DESIGNING POSITIONING IMPROVEMENT OF SILVI’S INSTAGRAM USING MULTIDIMENSIONAL SCALING - Putra, Muhammad Aldio Rozan; Suhendra, Agus Achmad; Kusmayanti, Ima Normalia (Journal of Production, Enterprise, and Industrial Applications, 2024)
Silvi is an application that helps restaurant owners in managing ordering and payment procedures. PT. Kreigan Sentral Teknologi markets the Silvi application through social media, and one of the platforms they use is Instagram. Potential clients can access the Silvi Application via IG called silvi.indonesia. The engagement rate shows that it is very important to control the feed on Instagram to get more engagement. By using multidimensional scaling, it was concluded that there are ten Instagram engagement attributes used in perceptual mapping, such as profile interest, profile description, feed interaction, feed interest, feed timeline, story timeline, story interest, text interest, and text explanation. There are nine competitors used in perception mapping. Based on the three regions on the map, Silvi is in region A with Moka and ESB. Recommendations for improving the Instagram SIlvi positioning design are carried out on the attributes that the company wants to highlight so that Instagram audiences can recognize and get more engagement on Instagram Silvi.